Exploring The Guardians’ Point of Views on Their Children’ Satisfaction and Behavioral Intention to Learn with Cartoon Animation in Sichuan, China - Zhong, Yu (Scholar: Human Sciences, 2024)
Purpose: This study aims to explore the guardians’ point of view on their children’s satisfaction and behavioral intention of cartoon animation in Sichuan, China. The research model was constructed to identify causal relationships between information quality, service quality, perceived usefulness, negative economic impacts, negative sociocultural, satisfaction, and behavioral intentions. Research design, data, and methodology: This study applied a quantitative method by distributing questionnaires to 500 guardians whose children are between grades 1 to 4 and engage with animation in a primary school. The sampling techniques involve judgmental and convenience sampling. Before the data collection, Item Objective Congruence (IOC) Index and the pilot test (n=50) with Cronbach’s Alpha were used. Data were analyzed through confirmatory factor analysis (CFA) and structural equation modeling (SEM). Results: The hypotheses testing was measured with a p-value<0.05. The results were that five out of six hypotheses were supported. Service quality significantly influences perceived usefulness. Perceived usefulness, negative economic impact, and negative sociocultural significantly influence satisfaction. Satisfaction significantly influences behavioral intentions. On the contrary, information quality has no significant influence on perceived usefulness. Conclusions: Animation developers, teachers, and school managers should improve high-quality cartoon animation and related tools to enhance children’s education.